UPAYA MENGATASI KESULITAN BELAJAR SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMP NEGERI 2 SUNGKAI UTARA LAMPUNG UTARA - Atieka, Nurul (Lembaga Penelitian UM Metro, 2016)
The purpose of this study is to know the results of the implementation of group counseling services in overcoming the difficulties of learners grade class VII.D Junior High School (SMPN) 2 North Sungkai Odd Semester Academic Year 2013/2014, guidance services group can overcome the difficulties of learners class VII .D SMPN 2 North SungkaiOdd Semester Academic Year 2013/2014. The study designs using follow-services research. The subject in this study is VII.D grade students of SMPN 2 North Sungkai Odd Semester Academic Year 2013/2014. With a number of 10 students from 36 students. The method used in collecting data by observation and field notes. The analysis of the data used quantitative and qualitative data. The results obtained through the implementation of group counseling services in overcoming the difficulties of learners class VII.D SMPN 2 North Sungkai Odd Semester Academic Year 2013/2014, is visible seen from the changes to learn and the ability of learners in understanding the subject matter, have the drive and the need to learn, to remember the subject matter well. Through group counseling services provided by the teacher BK can overcome the difficulties of learners grade class VII.D SMPN 2 North Sungkai Semester Odd Academic Year 2013/2014. There was a decrease of learning difficulties of students in the first cycle seen from the average percentage is 26.7% and the second cycle by 75%, leading to a decline in learning difficulties amounted to 48.3%.